Characterization of phenolic composition in chestnut leaves and beer residue by LC-DAD-ESI-MS. (May 2016) - Munekata, P.E.S.; Franco, Daniel; Trindade, M.A.; Lorenzo, José M.
Abstract: The phenolic profile of chestnut leaves extract (CHE) and beer residue extract (BRE) was analyzed in order to evaluate their potential application as a functional food ingredient using the LC-DAD-ESI-MS technique. A total of 15 compounds corresponding to flavonoids (quercetin and cirsiliol), phenolic acids (gallic, protocatechuic and vanillic acids) and lignans (medioresinol) were identified in CHE extract. Fourteen compounds were observed in BRE extract, including flavonoids (proanthocyanidin and catechin glucoside), phenolic acids (caffeic acid hexoside and syringic acid derivative) and bitter acids (lupulone, cohumulone and humulone). Among them, the flavonoids family was the largest group in both extracts, with 7 and 5 compounds in CHE and BRE, respectively. In conclusion, both extracts could be used as natural alternative source of natural antioxidant with potential applications in the food and health sectors. Highlights: Chestnut leaves (CHE) and beer residue extract (BRE) phenolic profile were evaluated. Flavonoids were the major group of phenolic compounds in CHE and BRE. CHE also presented phenolic acids and lignans. BRE phenolic profile showed phenolic acids and bitter acids. Contribution to phenolic characterization of chestnut leaves and beer residue.